Sistem Pendukung Keputusan Peserta Jaminan Kesehatan Daerah Dengan Metode SAW - Siti Monalisa; Nurul Fadila (UIN Sultan Syarif Kasim Riau, 2015)
Jaminan Kesehatan Daerah (Jamkesda) is a health care program developed by the local government in Dinas Kesehatan Kabupaten Kampar, in order to serve the public health Kampar. To determine the data collection Jamkesda Participants then deliver the data to the public from the village health centers, and health centers to check, channeling data to the Department of Health and Health Department to collect data on the verification and validation of the data to the village. This causes the length of the process of determining pesetas Regional Health Insurance, as well as in the selection process participant data manually Jamkesda frequent mistakes, including inaccuracies in determining participants underprivileged or poor.Decision support system (DSS) needed to be able to provide ease in the determination of the participants Jamkesda ranking results. Simple Additive Weighting (SAW) is a method to supports the assessment criteria and weighting. The criteria used are based on income, dependents, family size and poverty letter.The ranking results of sorted from the highest total score to lowest point total. With the decision support system will be beneficial to Dinas Kesehatan Kabupaten Kampar in the determination of the participants Jamkesda based on desired criteria.Keywords: Jamkesda, Ranking and Weighting ,SAW, SPK.